Training Management Analysis In Medical Service Training Program - Trisnawati, Wisda; Basabih, Masyitoh; Sigalingging, Basrin Harsono (Jurnal Riset Kesehatan, 2024)
Indonesia still faces a problem with the quality of its human resource for health, despite the potential for improvement through training. According to the Ministry of Health data from 2022, only 44,391 out of 1,440,130 healthcare workers (3%) received accredited training., with many lacking a proper management process. The purpose of this study is to analyze the management of health worker training at Medstrap, organized by Company X using the Analyze, Design, Develop, Implement, Evaluate (ADDIE) Model. Researcher uses a cross-sectional design with a qualitative approach and uses in-depth interviews, observation, and document review. The result are: The analysis phase of training lacks depth, making it difficult to identify clear objectives, which are essential for developing a training roadmap. In the design phase, the absence of a clear blueprint for learning objectives and materials impacts the selection of methods and resources. Delivery and time management are big problems that can be seen from the implementation of training, which is influenced by the ability of the presenter to communicate and master the participants. Evaluation is limited by inadequate time and presenter capabilities, making it hard to measure training outcomes effectively. These issues, particularly in the analysis phase, highlight the need for improvement in the Medstrap process.